Evaluation of reanalyzed surface air temperature over the western Tibetan Plateau - Jing Wang; Xiao-Feng Li; Jingzhi Wang; Xin Lai; Song Yang; Nathan Forsythe; Hayley J. Fowler (Atmospheric Research, 2026)

MutAnt: mutation annotation tool predicts deleteriousness of missense mutations and improves mutation calling from transcriptomics - Aleksandr Sarachakov; Anastasiya Yudina; Viktor Svekolkin; Anna Parfenenkova; Miryam Spektor; Polina Oshchepkova; Marina Pak; Zoia Antysheva; Linda Balabanian; Jessica H. Brown; Max Feinberg; Nathan Fowler; et al. (Human Genetics, 2025)

Stress testing water allocations across large river basins - Avril Horne; Andrew John; Keirnan Fowler; Ziqi Zhang; Rory Nathan (Climatic Change, 2025)
Water scarcity is a growing global challenge, with climate change exacerbating pressures on water security and allocation. Increasingly approaches such as stress testing, scenario neutral methods and decisions scaling are being suggested to identifying system vulnerabilities by systematically varying climate inputs to better understand the system response and thresholds of impacts. However, applying such approaches to large river basins presents technical challenges in making the computational process tractable. This study develops a novel, rapid-assessment method to stress test water allocations in large, complex river basins, applying it to the Southern Connected Murray-Darling Basin in Australia. The method combines stochastic climate projections, rainfall–runoff modelling, and statistical allocation modelling to evaluate how changes in precipitation, temperature, and runoff affect water availability and allocations. We assess the implications of spatial differences in climate, runoff response, and allocation policy across major rivers in the basin. Our results highlight substantial spatial variation in climate sensitivity and demonstrate that water allocation policy plays a critical role in mediating climate impacts. Among the three factors examined, the structure of the water allocation policy had the greatest influence on system robustness (i.e. is the inherent capacity of a system to withstand a range of conditions). This is particularly evident in the Murray reservoirs, where two different allocation systems produce markedly different outcomes under climate change. The approach offers a scalable framework for evaluating climate risks to water resources in regulated river systems worldwide, and an additional tool for rapid assessment of water allocation impacts in large river basins.

Mitigating impacts of climate change on flow regimes through management of small dams and abstractions - Robert Morden; Avril Horne; Rory Nathan; Nick R. Bond; Keirnan Fowler (Journal of Hydrology, 2025)

A synoptic view of the Western Tibetan Vortex - Binbo Lei; Xiao-Feng Li; Yanjie Li; Song Yang; Hayley J. Fowler; Nathan Forsythe (Atmospheric Research, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

A multi-objective optimization model for cropland design considering profit, biodiversity, and ecosystem services - Caleb H. Geissler; Nathan L. Haan; Bruno Basso; Ames Fowler; Douglas A. Landis; Tyler J. Lark; Christos T. Maravelias (Ecological Modelling, 2025)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

The time of emergence of climate-induced hydrologic change in Australian rivers - Andrew John; Rory Nathan; Avril Horne; Keirnan Fowler; Michael Stewardson; Murray Peel; J. Angus Webb (Journal of Hydrology, 2023)

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Downscaling climate change of mean climatology and extremes of precipitation and temperature: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Aidan Burton; Hayley J. Fowler; Stephen Blenkinsop; Stephen Birkinshaw; Nathan Forsythe; João P. Nunes; Elsa Sampaio (International Journal of Climatology, 2019)
Downscaling is usually necessary for robust hydrological impact assessments. This may be undertaken using a wide range of methods, including a combination of dynamical and statistical‐stochastic downscaling. This study uses the Spatial–Temporal Neyman‐Scott Rectangular Pulses model—RainSimV3, the precipitation‐conditioned daily weather generator—ICAAM‐WG, and the change factor approach for downscaling synthetic climate scenarios for robust hydrological impact assessment at middle‐sized basins. The ICAAM‐WG was developed based on the concept of the Climate Research Unit daily weather generator (CRU‐WG), motivated by the need for improved representation of heat waves by downscaling methods given the positive feedback between low soil moisture and high air temperature. We demonstrated the validity of the proposed methodology in the 705‐km 2 Mediterranean climate basin in southern Portugal. The results show that, for the control period 1980–2010, both RainSimV3 and ICAAM‐WG reproduced not only the mean climatology, but also extreme wet and low precipitation events, as well as the extremes of temperature and heat waves. We found that downscaling with ICAAM‐WG (SIM6), which uses second‐order autoregressive processes for the simulation of temperature during consecutive dry and wet days, outperformed ICAAM‐WG (SIM4), which used only first‐order autoregressive processes, leading to improved simulation of heat waves. ICAAM‐WG (SIM6) well reproduced observed heatwave extremes with return periods of up to 30 years; however, ICAAM‐WG (SIM4) overestimated these extremes substantially. This indicates the importance of incorporating second‐order autoregressive processes in the simulation of heatwave length. In the context of climate warming, the proposed methodology provides a tool to improve downscaled projections of future extremes with confidence intervals for not only wet events but also dry spells and heat waves.

Thermodynamic controls of the Western Tibetan Vortex on Tibetan air temperature - Xiao-Feng Li; Hayley J. Fowler; Jingjing Yu; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2019)

Primary central nervous system lymphoma in patients with and without HIV infection: a multicenter study and comparison with U.S national data - Dima Dandachi; Quinn T. Ostrom; Insun Chong; Jose A. Serpa; Thomas P. Giordano; Carol Kruchko; Jill S. Barnholtz-Sloan; Nathan Fowler; Rivka R. Colen; Fanny E. Morón (Cancer Causes & Control, 2019)

Downscaling climate change of water availability, sediment yield and extreme events: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Stephen Birkinshaw; Aidan Burton; Hayley J. Fowler; Nathan Forsythe; João Pedro Nunes; Elsa Sampaio; Francisco Lúcio dos Santos; Sandra Mourato (International Journal of Climatology, 2019)
A robust hydrological impact assessment is indispensable for mitigation and adaptation planning. This study presents an integrated modelling methodology for evaluating climate change impacts on water availability, sediment yield and extreme events at the catchment scale. We propose the use of the spatial–temporal Neyman–Scott Rectangular Pulses (STNSRP) model—RainSim V3 and the rainfall conditioned daily weather generator—ICAAM‐WG, as well as the physically based spatially distributed hydrological model—SHETRAN. The change factor approach was applied for obtaining unbiased rainfall and temperature statistics. The ICAAM‐WG was developed based on the modified Climate Research Unit daily Weather Generator (CRU‐WG). The methodology is proposed to generate synthetic series of hourly precipitation, daily temperature and potential evapotranspiration, hourly runoff and hourly sediment discharge. We demonstrated a possible application in a 705‐km 2 Mediterranean climate basin in southern Portugal. The case study showed the evaluation of future climate change impacts on annual and monthly water balance components and sediment yield, annual and seasonal flow duration curves, empirical extreme value distributions and the theoretical fits. It did not consider the possible uncertainty due to the limit of computational resources. The methodology can be well justified as follows: (a) the use of synthetic hourly instead of daily precipitation enables SHETRAN to be more capable of reproducing reliable storm runoff processes and the consequent sediment transport processes; (b) the use of SHETRAN makes possible the impact assessment to be accessible for any model grid square within the study basin; (c) the use of a statistical–stochastic downscaling method facilitates the generation of the synthetic series with unlimited length. It makes possible robust hydrological impact assessments if uncertainties related to the global climate model, regional climate model, greenhouse gas emission scenario, downscaling method, hydrological model and observational data are considered.

The Karakoram/Western Tibetan vortex: seasonal and year-to-year variability - Xiao-Feng Li; Hayley J. Fowler; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2018)

Foraging distribution of a tropical seabird supports Ashmole’s hypothesis of population regulation - Steffen Oppel; Annalea Beard; Derren Fox; Elizabeth Mackley; Eliza Leat; Leeann Henry; Elizabeth Clingham; Nathan Fowler; Jolene Sim; Julia Sommerfeld; Nicola Weber; Sam Weber; et al. (Behavioral Ecology and Sociobiology, 2015)

Opportunities from Remote Sensing for Supporting Water Resources Management in Village/Valley Scale Catchments in the Upper Indus Basin - Nathan Forsythe; Hayley J. Fowler; Chris G. Kilsby; David R. Archer (Water Resources Management, 2012)

Viral and non-viral risk factors for non-Hodgkin’s lymphoma in Egypt: heterogeneity by histological and immunological subtypes - Lenka Goldman; Sameera Ezzat; Nadia Mokhtar; Amany Abdel-Hamid; Nathan Fowler; Iman Gouda; Soheir Abdel Latif Eissa; Mohamed Abdel-Hamid; Christopher A. Loffredo (Cancer Causes & Control, 2009)